Integrative multi-omic analysis of NLRP3 inflammasome dysregulation and subtyping for personalized treatment in acute myeloid leukemia - Hong Zhang; Linlin Yang; Yukexin Liu; Dongju Wang; Liming Shi; Changyu Tian (Discover Oncology)
Abstract Acute myeloid leukemia (AML) is a devastating form of blood cancer characterized by uncontrolled growth and impaired maturation of myeloid precursor cells in the bone marrow. Despite advancements in treatment strategies, the prognosis for AML patients remains poor. The NLRP3 inflammasome, a multi-protein complex involved in innate immunity and inflammation, has been implicated in various diseases; however, its role in AML development and progression is not well understood. In this study, we analyzed genomic, bulk-, and single-cell transcriptomic data to assess the contribution of NLRP3 inflammasome genes to AML. Results suggested that 28 NLRP3 inflammasome genes with clinical implications were dysregulated in AML. Notably, we identified seven prognosis-related genes: CASP1, CPTP, MEFV, NFKB2, PANX1, PYCARD, and SIRT2. To further investigate the functional relevance of NLRP3 inflammasome genes, we developed an NLRP3 score (Nscore) based on the expression levels of these seven genes. We identified four dysregulated gene clusters that distinguished high- and low-Nscore groups, enabling the identification of two distinct AML subtypes, with subtype 2 exhibiting worse overall survival than subtype 1. Additionally, using a network-based approach, we identified 62 NLRP3 inflammasome-related genes and constructed a risk score model with COL2A1, ITGB2, and SRC genes, providing a comprehensive assessment of patient risk stratification. We revealed a positive correlation between the Nscore and macrophage M1, suggesting potential drug response mechanisms. Based on the identified AML subtypes and their distinct mutational landscapes, we predicted potential treatment options, with Paclitaxel, Afuresertib, and Mitoxantrone emerging as potential therapeutic agents for the AML subtypes.